1999
DOI: 10.1007/bf02318379
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system disorders in stroke

Abstract: Disturbances of the autonomic nervous system are common in patients with various cerebrovascular diseases. They are attributed to damage of the central autonomic network, particularly in the frontoparietal cortical areas and in the brain stem, or to a disruption of the autonomic pathways descending from the hypothalamus via the mesencephalon, pons, and medulla to the spinal cord. The most common clinical problems include abnormalities in heart rate and blood pressure regulation, reflecting cardiovascular auton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 91 publications
(127 reference statements)
4
83
1
7
Order By: Relevance
“…In the current study, 30‐minute tMCAO had an impact on autonomic regulation (see Fig 5), due to a direct lesion of the right insular cortex area (see Fig 1), or—in cases without macroscopic lesion detection—alternatively due to ischemic disruption of the autonomic pathways downstream of the insula that led to cardiac dysfunction development in comparison to left‐sided insular cortex lesions (see Fig 2). 44 As sympathetic overactivity is associated with myocardial injury and cardiac dysfunction up to heart failure development,40, 41, 43 it could be the missing link between IS and chronic cardiac dysfunction. In contrast to reports showing acute cardiac dysfunction after stroke,7 until now, no study has specifically investigated chronic development of systolic dysfunction after IS.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 30‐minute tMCAO had an impact on autonomic regulation (see Fig 5), due to a direct lesion of the right insular cortex area (see Fig 1), or—in cases without macroscopic lesion detection—alternatively due to ischemic disruption of the autonomic pathways downstream of the insula that led to cardiac dysfunction development in comparison to left‐sided insular cortex lesions (see Fig 2). 44 As sympathetic overactivity is associated with myocardial injury and cardiac dysfunction up to heart failure development,40, 41, 43 it could be the missing link between IS and chronic cardiac dysfunction. In contrast to reports showing acute cardiac dysfunction after stroke,7 until now, no study has specifically investigated chronic development of systolic dysfunction after IS.…”
Section: Discussionmentioning
confidence: 99%
“…It hasbeen suggested that clinically important OH is not common after stroke (Korpelainen et al, 1999) as it is with other populations, such as spinal cord injury or Parkinson's (Velseboer et al, 2011) where the clinical and health implications of OH is well established. However, with the combined occurrence of over 20% of participants demonstrating OH or hypotensive symptoms, we believe that orthostatic intolerance is prevalent and clinically important after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Translocation of gut bacteria after stroke has also been documented. [9][10][11] However, it is currently unclear whether brain injury has organ-specific effects, which could be revealed with imaging techniques in vivo.…”
Section: Introductionmentioning
confidence: 99%